2011
DOI: 10.1088/0022-3727/44/4/045204
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the body force field of plasma actuators

Abstract: A novel technique is proposed and investigated for the estimation of the body force field resulting from the operation of a dielectric barrier discharge plasma actuator. The technique relies on the measurement of the spatio-temporal evolution of the induced velocity field using high-speed particle image velocimetry (PIV). The technique has the advantage of providing spatial distribution of the body force vector field. A full Navier-Stokes term decomposition is applied on the evolving field along with additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
95
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(102 citation statements)
references
References 28 publications
7
95
0
Order By: Relevance
“…For estimatingĨ at each voltage, PIV measurements are carried out in quiescent conditions with the actuator operating continuously atf c = 5kHz.Ĩ is then calculated as described by Kotsonis et al (2011) to the appropriate control volume, assuming uniform pressure distribution. It should be noted here, that the described momentum coefficient is calculated based on continuous operation of the actuator and, as such, pertains to the mechanical power of the actuator.…”
Section: Ac-dbd Forcingmentioning
confidence: 99%
“…For estimatingĨ at each voltage, PIV measurements are carried out in quiescent conditions with the actuator operating continuously atf c = 5kHz.Ĩ is then calculated as described by Kotsonis et al (2011) to the appropriate control volume, assuming uniform pressure distribution. It should be noted here, that the described momentum coefficient is calculated based on continuous operation of the actuator and, as such, pertains to the mechanical power of the actuator.…”
Section: Ac-dbd Forcingmentioning
confidence: 99%
“…The technique is based on the periodicity of the plasma forcing effect as proved in numerous previous studies. 16,17 More specifically, the sampling rate f s is kept fixed at 6 kHz while the actuator carrier frequency f ac is chosen such that the ratio r ¼ f s /f ac is not an integer value. In this manner, the phase of every measured point is slightly shifted between successive actuation signal cycles.…”
Section: -2mentioning
confidence: 99%
“…This point has been discussed in Brauner et al [28] and it was shown that the pressure gradient can contribute to the mean EHD volume force. The contribution of the pressure gradient in the computation of the EHD force has also been partially discussed in the pioneering work of [22]. It was shown that convection and pressure gradient are initially negligible, but the influence of the pressure gradient can increase with time.…”
Section: Iii-1 Principle Of Piv-based Estimation Of the Volume Ehd Forcementioning
confidence: 99%
“…The most straightforward strategy for evaluating the EHD volume force is based on the two-dimensional incompressible Navier-Stokes equations. Assuming that the pressure gradients are much smaller that the force components, they can be neglected as initially proposed in [21] and because all the other components of the Navier-Stokes equations can be computed from the experimental data, the 2D spatial distribution of the mean force component can be evaluated fairly easily [22][23][24][25]. In most of the cases, time-averaged velocity fields are measured, but phase-averaging procedure can also be used to recover the dynamic aspects of the EHD volume force [26][27].…”
mentioning
confidence: 99%